Large genetic distances among Aedes aegypti populations along the South Pacific coast of Mexico - Lozano Fuentes, Saúl; Fernández Salas, Ildefonso; Beaty, Barry J.; Black, William C.; García, Franco F.; Muñoz, María de Lourdes (American Society of Tropical Medicine and Hygiene, 2002)
A population genetic analysis was conducted among 20 Aedes aegypti collections from 19 cities along the south Pacific coast in the Mexican states of Guerrero, Oaxaca, and Chiapas and in Coatepeque, Guatemala. Genetic variation was scored at 131 random amplified polymorphic DNA loci. The amount of genetic differentiation among collections was approximately 3 times as great as detected among collections in an earlier study in northeastern Mexico. Regression analysis of linear or road distances on linearized F(ST) indicated that collections are genetically isolated by distance. Cluster analysis failed to group collections in geographic proximity, and there was as much genetic variation among collections 60 km apart as there was among all collections (approximately 900-km range). The large genetic differentiation in southern Mexico reflects reduced gene flow among mosquitoes arising in a greater diversity of habitats and altitudes than exists among northeastern collections. It is likely that dispersal via human commerce in the northeast confounds patterns of natural gene flow.